A new Patagonian long-lived species of Cyclochlamys Finlay, 1926 (Bivalvia: Pectinoidea) - Pastorino, Roberto Santiago Guido (2018)
A new species of the bivalve family Cyclochlamydidae is described from the southwestern Atlantic in Argentine waters. Cyclochlamys argentina sp. nov. is the second representative of the genus known to live in the Magellanic area. In addition, this long-lived species is also recorded from lower Miocene rocks in the province of Santa Cruz exposed along the Atlantic coast of the Monte León National Park. The material was collected from the Punta Entrada Member of the Monte León Formation. These small mollusks clearly belong in Cyclochlamys because of shell characters such as the irregularly pitted prodissoconch I and right valve with commarginally elongated rectangular prisms over most of disc. Cyclochlamys argentina sp. nov. shows affinities with taxa such as C. aupouria and C. shepherdi, all of which are known from areas of New Zealand.